Survey of particle production rates from process activities in pharmaceutical and biological cleanrooms. (3rd July 2019) - Ogunsola, Oluwaseyi T.; Wang, Junke; Song, Li
Abstract : The lack of measurement data on particle generation rates from process activities for companies involved in the life sciences industry, such as pharmaceutical and biotechnology firms, has the potential to undermine cleanroom design, particulate concentration control, and energy efficiency. Based on this situation, this paper surveys the particle production rates from process activities in pharmaceutical and biological cleanrooms using field measurements for the particle sizes of interest (0.3 µm, 0.5 µm, and 1 µm). The measured and collected data were correlated to the surveyed activities to obtain a range of particle generation rates for different cleanroom operations. In terms of the recommended ACH values and measured ACH values, the results indicate that although most cleanrooms operate below the recommended ranges, in most cases they satisfy or exceed the required ISO standard cleanliness levels. In addition, the particle generation rates are process-specific and that suggests process-specific guidelines for different cleanrooms will help engineers, owners and contractors arrive at a better design solution. It is worth mentioning that nonperfect mixing of airflow and particles was observed in several cleanrooms, resulting in large variances in the measurements at different sampling locations. This observation suggests that a correction factor might be needed for the ventilation effectiveness for Class 7 and 8 cleanrooms. Although the determination of the correction factor is beyond the study of this paper, the data presented in this paper are critical to understand the severity of the non-perfect mixing in Class 7 and 8 cleanrooms and thus provides insights on the determination of the correction factor. The research reported in this paper was conducted through the ASHRAE 1399 research project, with a focus on developing scientific cleanroom design guidelines that can assist engineers, owners, and contractors to arrive at appropriately sized and efficient cleanroom systems.